EVALUASI PENGGUNAAN APLIKASI RENCANA KEGIATAN ANGGARAN SEKOLAH (RKAS) DAN REALISASI ANGGARAN TERHADAP HASIL AUDIT DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DALAM PENCEGAHAN FRAUD SMK NEGERI 03 KEPAHIANG - aprilia, sely; riswandi, pedi; Yulianasari, nina (Jurnal Ilmu Akuntansi, 2024)
This research aims to determine the evaluation of the use of the School Budget Activity Plan (RKAS) application and budget realization on the audit results of school operational assistance funds (BOS) in preventing fraud at SMK Negeri 03 Kepahiang. Samples were taken using the saturated sampling method. The samples used were reports on the use of BOS funds for 2021-2023, RKAS Application data, interview results from school principals, school treasurers, school committees and interviews from the Bengkulu Province Education and Culture Office. The data analysis techniques used are data collection, data reduction, data presentation and data verification. Based on the research results, it shows that the use of the RKAS application helps in improving the management of the BOS Fund budget. And the realization of an appropriate budget and in accordance with planning contributes to reducing the potential for fraud.